Kinetic Potentials of the Effect of Ethanol on Calcium Content of Ashed Cow Bones (Journal of Basic and Applied Research in Biomedicine, 2022)
The kinetic study was carried out to determine the calcium content in the ashed cow bone extract and to monitor the rate of deterioration of the calcium content in the presence of alcohol. The cow bone was subjected to pre-treatment processes such as drying, grinding, and ashing. The ashed cow bone was digested in distilled water for 24 hours and then filtered. The calcium extract was determined by titration and a concentration of 86.67 mg/l of calcium was recorded. Kinetic studies were carried out by introducing equal volumes of local ethanol into the standard solution of the calcium and measuring the rate of reaction titrimetrically after every 10 minutes interval. The added ethanol led to a gradual decrease of the concentration of calcium with increase in time. The average pH of the reaction mixture was 7.01. Other kinetic parameters such as rate of reaction, reaction constants, order of reaction, half-life and full life of the kinetics of the effect of ethanol on calcium content of the ashed cow bone was determined. The rate of reaction obtained was 0.63 mg/l/min. The rate constant value obtained was 0.00027272 mg/dm3/min. The kinetics revealed a second order integrated rate law. A half-life of 42.3 minutes was determined which is equivalent to a full life of 84.m minutes. Discussions are made based on the dangers of alcohol intake to the calcium contents of the body.